Tonal Structure of the Ideophones in Meetto-Makhuwa of Southern Tanzania - Ismail , Joseph Hokororo (African Journal of Education,Science and Technology (AJEST), 2018)
This study investigates the tone structure of Ideophones in Meetto-Makhuwa language and the extent of which ordinary words differ with that of ideophones. The analysis of tone in ordinary words in Makhuwa has been discussed in a series of papers, see for examples: (Cheng & Kisseberth, 1979, 1980, 1981), but the study of tone in ideophones has not been investigated. Relevant facts on the tonal structure of ideophones have not been exhaustively investigated. The paper aims to analyze tone in ideophones and compare it to that of ordinary words specifically to simple infinitives in Meetto-Makhuwa and discuss tonal processes and/or rules that operate in Meetto-Makhuwa ordinary words as compared to that of ideophones. The significance of the study rests to the fact that, Meetto is one of the dialects of Makhuwa, this study will be an important source in the field of comparative studies of ideophones in Makhuwa dialects. In this descriptive account, the study employed autosegmental framework as applies by Robert (1992).It is observed that in ordinary word no H tone appears at the end of a word whereby in ideophonic form, H tone may occur. Therefore, this study contributes to our understanding of differences in tonal structure between in ordinary words as compared to that of ideophonic forms in Makhuwa as well as other closely Bantu languages.